Formulasi Gel Pengelupas Kulit Mati yang Mengandung Etil Vitamin C dalam Sistem Penghantaran Macrobead® - MARLINE ABDASSAH; TAOFIK RUSDIANA; ANANG SUBGHAN; GUSTIN HIDAYATI (JURNAL ILMU KEFARMASIAN INDONESIA, 2009)
To recover good appearance of skin, dead skin cells should be removed, among others by using exfoliating agent, and to preserve the fresh skin ethyl vitamin C could be used as an antioxidant. Formulation and evaluation of skin exfoliating gel containing ethyl vitamin C in Macrobead® delivery system, using acrylates copolymer and carboxy vinyl polymer as gel bases have been carried out. The gel evaluation included physical evaluation and safety examination. The results showed that ethyl vitamin C could be trapped into Macrobead® system with good absorption inthe ratio of active content and Macrobead® of 3:4. Based on the physical evaluation of the gel formula, it was found that formula with acrylates copolymer base has altered the consistency and homogenity of gels, but not the formula with carboxy vinyl polymer base. Gels using carboxy vinyl polymer showed good physical stability for28 days of storage. The safety evaluation indicated that the preparation was safe to be used for it did not cause irritation on consumers skin. The examination showed that the preparation could exfoliate dead skin cells and thus freshen the users’ skin effectively.